Dasatinib in the Management of Pediatric Patients With Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia - Cerchione, Claudio; Locatelli, Franco; Martinelli, Giovanni (Frontiers in Oncology, 2021)
Acute leukemia is the most common cancer in childhood; in particular, acute lymphoblastic leukemia (ALL) represents roughly up to 80% of all cases of acute leukemias in children. Survival of children with ALL has dramatically improved during the last decades, being nowadays over 90% (versus 40% of adult patients) in the developed countries, excepts in infants (i.e., children < 1 year), where no significant improvement was registered. Philadelphia positive ALL (Ph+ALL) accounts for around 3% of cases of childhood ALL, its incidence increasing with patient’s age. Before tyrosine-kinase inhibitors (TKIs) era, pediatric Ph+ALL showed a worse prognosis in comparison to other forms of ALL: it was managed with intensive chemotherapy, followed, whenever possible, by allogenic hematopoietic stem cell transplantation (HSCT) in first morphological complete remission. TKIs have totally revolutionized current clinical approach: combinations of imatinib plus standard chemotherapy can abrogate the negative prognostic impact conferred by the presence of BCR/ABL1 rearrangement, resulting into a probability of event-free survival (EFS) significantly better than that recorded in the pre-TKI era. Long-term follow-up confirmed these data, questioning the role of a real advantage offered by HSCT over intensive chemotherapy plus TKI in all Ph+ALL pediatric patients. Imatinib was the first generation TKI and the prototype of targeted therapy, but over the years second- (dasatinib, nilotinib, bosutinib) and third-generation (ponatinib) TKIs showed capacity to overcome resistance to imatinib in Ph+ hematological neoplasms. Given the effectiveness of the first-in-class TKI, imatinib, also the second-generation TKI dasatinib was incorporated in the treatment regimens of Ph+ALL. In this manuscript, we will discuss the role of this drug in pediatric Ph+ALL, analyzing the available data produced so far.